A Preliminary Survey of Plankton in Irrukkangudi Reservoir, Virudhunagar District, T.N., India - M.K. Rajan2, V. Kanagasabapathi1* and (Journal of Phytology, 2010)
Aquatic organisms, especially plankton from the most sensitive component of the ecosystem and signal environmental disturbances. Apart from primary production, phytoplankton play an important role as food for herbivorous animals and act as biological indicators of water quality in pollution studies. Zooplankton occupy a vital role in the trophic structure of an aquatic ecosystem and play a key role in the energy transfer. The inadequate knowledge of plankton and their dynamics is a major handicap for the better understanding of the life process of fresh water bodies. Hence the present investigation was carried out a newly constructed water reservoir, (Sattur Taluk, Virudhunagar District, Tamilnadu) Irrukkangudi reservoir for a period of eight months from August 2005 to March 2006. The surface samples of water were collected following standard methods and phytoplankton zooplankton were identified using standard keys. The phytoplankton and zooplankton diversity were studied during the period of this investigation. Twenty six different species of phytoplankton belonging to six classes were identified. Twenty five different species of zooplankton belonging to four classes Rotifera, Cladocera, Ostracoda and Copepoda were identified.